2020
DOI: 10.1002/ehf2.12909
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive test results are associated with mortality and rehospitalization in heart failure: Swedish prospective cohort study

Abstract: Aims We aimed to search for associations between cognitive test results with mortality and rehospitalization in a Swedish prospective heart failure (HF) patient cohort. Methods and results Two hundred and eighty-one patients hospitalized for HF (mean age, 74 years; 32% women) were assessed using cognitive tests: Montreal Cognitive Assessment (MoCA), A Quick Test of Cognitive speed, Trail Making Test A, and Symbol Digit Modalities Test. The mean follow-up time censored at rehospitalization or death was 13 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 31 publications
(74 reference statements)
1
35
0
2
Order By: Relevance
“…At the time of study enrolment (before hospital discharge) the patients were screened for cognitive impairment using the Montreal Cognitive Assessment (MoCA) and during the 1-year follow-up hospital readmissions, deaths and days at home were recorded. Confirming prior studies, 6 poorer cognitive function was prevalent and independently associated with worse outcomes. On the other hand, the HF-DMP was independently associated with better outcomes, a finding that had also been previously documented.…”
supporting
confidence: 86%
“…At the time of study enrolment (before hospital discharge) the patients were screened for cognitive impairment using the Montreal Cognitive Assessment (MoCA) and during the 1-year follow-up hospital readmissions, deaths and days at home were recorded. Confirming prior studies, 6 poorer cognitive function was prevalent and independently associated with worse outcomes. On the other hand, the HF-DMP was independently associated with better outcomes, a finding that had also been previously documented.…”
supporting
confidence: 86%
“…This might be mainly attributed to the vulnerability and frailty of patients with lower cognitive function. Several studies have reported that poor cognitive function is associated with a significantly increased risk of mortality (14,(28)(29)(30)(31). Patients with poor cognitive function tended to have poor health literacy and less healthy lifestyles (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of brain health, the concept of "cognitive reserve" refers to the capacity of the brain to buffer age-related changes or even neurodegenerative pathology, thereby minimizing clinical manifestations (e.g., cognitive failures) that would be otherwise more apparent during cognitively demanding tasks (i.e., "brain stressors") (Kraal et al, 2021). For instance, cognitive tests have been demonstrated to predict outcome in older patients with heart failure (Holm et al, 2020). It has been hypothesized that this reserve capacity may not only derive from an individual's "anatomic" neural profile (e.g., cell count, synaptic connections, brain volume), but also in the effective physiological recruitment of neural networks and cognitive processes that are also supported by non-neural systems.…”
Section: Physiological Modeling Of Frailty and Resilience In Aging Adults: Current Approachesmentioning
confidence: 99%